SEASONAL REPRODUCTIVE CYCLE AND VARIABILITY IN PLASMA TESTOSTERONE LEVELS IN THE DOMESTIC DUCK (Anas platyrhynchos) - Simoes, Karina; Orsi, Antonio Marcos [UNESP]; Schimming, Bruno Cesar [UNESP]; Benetti, Edson Jose (Univ Federal Uberlandia, 2017)
Morphofunctional gonadal alterations constitute an annual cycle in birds during which four phases can be distinguished in the testes based on histological modifications in the seminiferous epithelium, called quiescence, recrudescence, reproduction and regression. The aim of the present investigation was to conduct a morphometric and morphological study of the seminiferous epithelium on the testis of domestic duck and to evaluate the plasma testosterone levels in order to determine the possible presence of a reproductive cycle in the tropical region. The study was conducted on 60 adult domestic ducks (Anas platyrhynchos), where five animals were sacrificed per month and the testes were removed and histologically and morphometrically studied. Blood samples of the five animals were collected monthly in the morning period and the testosterone levels were analyzed. Annual reproductive cycle of the domestic duck presented by four distinct phases, starting with the reproductive phase at the beginning of winter (July) and peak of reproduction in spring (October), accompanied by an increase in tubule seminiferous diameter, epithelium height, weight and testicular volume, followed by a regressive phase at the end of spring (November) and the beginning of summer (December). Testicular quiescence was observed during summer (January and February) and was followed by a phase of spermatogenic recrudescence, which lasted throughout autumn (March to June), corresponding to the longest phase of the cycle. Complete spermiogenesis in terms of spermatozoa maturation and spermiation was observed during the reproductive phase, coinciding with the plasma testosterone peak. At regressive phase an exfoliation of the seminiferous epithelium was observed, accompanied by a great amount of fibrillar collagen. A decrease in tubular seminiferous diameter and epithelium height was observed during testicular quiescence, with predominance of spermatogonia and Sertoli cells and a second plasma testosterone peak was also observed during this phase (January), probably representing the preparation for a gradual return to the spermatogenic process during recrudescence. The latter phase was characterized by gradual recovery of the seminiferous epithelium, accompanied by the increase of spermatogonia, onset of meiosis, and the presence of primary spermatocytes and maturing spermatids. In conclusion the domestic duck presented the testicular cycle divided in four distinct phases in the tropical region with testosterone peaks in the testicular quiescence and reproductive phases.
Keywords: Reproductive cycle; Testosterone; Domestic duck